La pédagogie des compétences dans le primaire catholique ivoirien - Rodrigue N'sanman
Due to the introduction of globalization in Subsaharian Africa, an appropriate management has been introduced in schools. The World Bank expects efficiency in the educational systems through the teaching of skills. When you look at the results, the catholic primary school system of the Ivory Coast Republic seems to rank at the top. Despite precarious and unsatisfactory conditions, teachers are earnestly zealous at work. And this, of course, reinforces the tendency of the hierarchy to consider the staff as being docile. In actual fact, this is far from being the case. So as to be efficient in the end, teachers often wring and distort the recommendations. They have their own values and arguments to teach with alternative methods which finally turn out to be efficient. Yet this questions both the management and the official prerequisites.